SISTEM INFORMASI MONITORING PERANGKAT DAN LINK GPON DUAL HOMING NODE B DI PT.XYZ - Ari Sujarwo; Muhammad Wijdan Fauzi (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Dual Homing ONT mechanism implemented by PT. XYZ to establish Node B BTS network. This mechanism has reliability benefit due to dual uplinks support it has, so when one of the dual uplinks goes down, the backup link will then getting active and forwarding data. At this time, current market available monitoring system unable to detect failure on both uplinks when one of them inactive due to system failure. This problem occurs because device probing could only be established up to ONT. In this case, engineer does not aware whether their link is up or not, and dual homing scheme does not really works. Due to problem which is explained above, this paper offers a new approach to monitor two target of each ONT: the IP address and the logical port of the OLT where the ONT connected. In this mechanism, if one of the link fail, system will send an alert to engineer based on the status of the logical port to repair the broken link.